The effectiveness of using powerpoint for teaching vocabulary to increase the vocabulary knowledge for the reading skill among the students of the intermediate intensive english I of semester II 2011 at The Foreing Languaje Department in The University of El Salvador - De León Pérez, Mirna Azeyadé; García de Angulo, Dora Cecilia; Cabrera Martínez, Ricardo; Ayala,Edgar Nicolas (San Salvador, El Salvador : Universidad de El Salvador, 2013)
A multimedia tool can be an innovative and complementary technique to teach vocabulary for the reading skill at the Foreign Language Department of the University of El Salvador. This tool is called PowerPoint. It is a presentation software program that allows users to make use of images, colored texts with simple animation (Microsoft, 2006). In the past decades, PowerPoint has been used in business to present graphics and general information. However, PowerPoint can be used today by language teachers as an effective and innovative technique to teach vocabulary and educators may be able to substitute the traditional techniques which teachers usually use in the form of flashcards, pictures, pictionaries and others. The purpose of this research is to present the effectiveness of using PowerPoint, to teach vocabulary to increase the vocabulary knowledge for the reading skill, with the Intermediate Intensive English I students of the Foreign Language Department of the University of El Salvador.
Incluye anexos.
Tesis para optar al título de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2013
Bibliografia : hoja 68
Keywords: Inglés -- Enseñanza